Religion and politics: an approach to role of the Catholic Church in Peru from the war with Chile to the present day - Trelles Velásquez, Gustavo (2021)
The Catholic Church in Peru has played a political role in various decision-making spheres within Peruvian society. During the period of the Peruvian independence, the Catholic Church kept a low profile and was rejected by the dominant political sector with a liberal tendency. However, such prominence arose after the war with Chile when due to the presidency of Nicolas de Piérola and the actions of the Lima widows, the resurgence of this organization was achieved. In this scenario, the Catholic Church in Peru would beginto show itself to the population as an organizing entity, protector of women and at the same time as a defenderof a social politics based on charity and on others. This new role would be reinforced throughout the20th century due to the application of an organization and structure policy of the Peruvian society. We willsee this in the political, social, and cultural articulation that the Catholic Church had with the differentparticipants and social agents in Peru. During the period of terrorism in Peru, the Catholic Church playeda role as mediator and protector of human rights that had been violated by both, the government forces,and the terrorists. Finally, at the beginning of the 21st century, we will see its ability to gather people tosupport or disapprove policies given by the governments on duty; for instance, «the March for Life» thatbrought together different conservative political forces to avoid the approval of abortion